Opening up? Exploring motives and needs of students and staff of a Dutch university on disclosing mental health issues to inform decision aid development - Yil Engbersen-Severijns; Daniëlle N. Zijlstra; Sanne E. M. Brouwers; Femke M. den Uil; Véronique Vancauwenbergh; Thomas Gültzow (PLoS ONE, 2025)
Background Decisions about disclosing mental health issues can be difficult, especially in the university setting. For this reason, students and staff of universities might benefit from decision support tools, such as the use of a decision aid. Currently, little is known about if and how people in this setting disclose and how decision support should look like. This study aims to address this gap by exploring disclosure experiences and preferences for support. Methods Semi-structured interviews were conducted with staff (n = 10) and students (n = 10), including participants who decided to (not) disclose their mental health condition. The participants were asked to complete a short questionnaire. Subsequently, they were interviewed about the decision to disclose and their needs regarding a potential disclosure decision aid. Interviews were analyzed using the Framework method. Results Most students chose not to disclose, whereas most staff did. Students and staff described advantages and disadvantages of disclosing. Reported advantages included support, relief, understanding, and safety. Risks included (fear of) stigmatization and career concerns. Not disclosing can prevent unwanted questions but can also lead to misunderstandings. Regarding decision support, both students and staff preferred a brief online tool. Conclusion In conclusion, both students and staff encounter challenges when it comes to deciding whether to disclose their mental health status. A decision aid can be a valuable tool to support them in making their decision.